Inovasi Pembelajaran Praktikum Akuntansi Perusahaan Jasa Dagang Berbasis Entrepreneur Project untuk Menyongsong Kampus Merdeka - Yulihanita, Aprilia; Ismoyo, Ananda Gilang; Sari, Eka Dia Permata (Jurnal Pendidikan Akuntansi (JPAK), 2022)
This study aims to generate and analyze the feasibility of a learning innovation design in the Entrepreneur Project-based Accounting Practicum for Trading Service Companies for students of the Accounting Education Study Program, State University of Surabaya. This research is included in the type of research and development or called Research and Development (R&D) model IDI (Instructional Development Institute) which was adapted from the University Consortium Instructional Development and Technology (UCIDT). The data analysis used is a descriptive statistical approach. The IDI development model that the researcher uses applies three major stages, namely defining, developing, and evaluating. The instrument used is an expert validation sheet. The results of this study are the design of learning innovations for accounting practicum courses for trading companies based on entrepreneur projects in one semester which have been validated with the results getting a good rating of 57.1% and a very good rating of 42.9%. This means that it can be concluded that the innovation of accounting practicum learning for trading service companies based on the entrepreneur project can be declared feasible to be continued at the implementation stage.